(untitled) (Journal of Parents and Teachers, 2024)
The article focuses on the experiences of those living in poverty, particularly children who have suppressed their urge to cry because, at some point, a family member was being killed. All of this leads to a completely different use of language, shaped by their experiences and circumstances.